2021
DOI: 10.3390/math9111180
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Software Defect Prediction Using Deep Learning

Abstract: Defect prediction is one of the key challenges in software development and programming language research for improving software quality and reliability. The problem in this area is to properly identify the defective source code with high accuracy. Developing a fault prediction model is a challenging problem, and many approaches have been proposed throughout history. The recent breakthrough in machine learning technologies, especially the development of deep learning techniques, has led to many problems being s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 53 publications
0
17
0
1
Order By: Relevance
“…The development of a software defect detection model with high accuracy has proven to be a herculean task. Over the past decade, several approaches have been proposed, but most of them have not been able to meet the standards in their accuracy of predicting and detecting the defects [17,18]. According to [19], the introduction of network computing technologies like cloud computing has provided users all around the world with an affordable and flexible network-based service provision scheme.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of a software defect detection model with high accuracy has proven to be a herculean task. Over the past decade, several approaches have been proposed, but most of them have not been able to meet the standards in their accuracy of predicting and detecting the defects [17,18]. According to [19], the introduction of network computing technologies like cloud computing has provided users all around the world with an affordable and flexible network-based service provision scheme.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of a software defect detection model with high accuracy has proven to be a herculean task. Over the past decade, several approaches have been proposed, but most of them have not been able to meet the standards in their accuracy of predicting and detecting the defects [5,12]. According to [24]], the introduction of network computing technologies like cloud computing has provided users all around the world with an affordable and flexible network-based service provision scheme.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a similar study, Naseem, Khan [41] explored the performance tree-based classifiers for SDP. Also, Akimova, Bersenev [42] experimented with the performance of deep learning methods in SDP. Findings from these studies indicated that ML approaches can be utilized for detecting defects in SDP processes.…”
Section: Related Workmentioning
confidence: 99%